2007
DOI: 10.1159/000112463
|View full text |Cite
|
Sign up to set email alerts
|

Reported Hearing Impairment in Essential Tremor: A Population-Based Case-Control Study

Abstract: In a population-based sample, we determined whether a larger proportion of essential tremor (ET) cases reported hearing impairment compared with controls. Ninety-six (38.7%) of 248 ET cases versus 1,371 (29.4%) of 4,669 controls (p = 0.002) reported hearing impairment. In a logistic regression analysis adjusted for age, gender, educational level, depressive symptoms, and dementia, participants who reported hearing impairment were 30% more likely to suffer from ET than were controls (odds ratio 1.3; 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 25 publications
3
43
1
3
Order By: Relevance
“…1,2 In addition to action tremor and other motor features, recent studies report nonmotor features. [3][4][5] In a growing number of studies, mild cognitive problems are being observed in ET cases. [6][7][8] Furthermore, an association between ET and dementia was reported in a recent population-based study in central Spain.…”
mentioning
confidence: 99%
“…1,2 In addition to action tremor and other motor features, recent studies report nonmotor features. [3][4][5] In a growing number of studies, mild cognitive problems are being observed in ET cases. [6][7][8] Furthermore, an association between ET and dementia was reported in a recent population-based study in central Spain.…”
mentioning
confidence: 99%
“…ET predominantly involves hands and may also spread to head, vocal cords, lips, and rarely to lower extremities [12,13]. Recently, it has been reported that hearing is impaired in patients with ET [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that mild cognitive impairment, personality changes, and olfactory nerve dysfunction may be associated with ET [2,3]. Recent studies have also demonstrated an association between ET and hearing impairment [4][5][6]. Ondo et al [4] also found that ET patients had an increased hearing disability compared to patients with Parkinson's disease (PD) and normal controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging evidence of recent years has changed the classical view of ET as a monosymptomatic condition, characterized by a kinetic arm tremor, to include a mixture of previously unrecognized motor and nonmotor problems [9,15,16,17,18]. Several studies have been performed comparing functional neuroimaging in ET and PD patients, and suggest that, as ET progresses, dysfunction in the nigrostriatal system may become more apparent and may contribute to parkinsonian symptoms of neurodegeneration [19].…”
Section: Discussionmentioning
confidence: 99%